Routine versus selective use of a femoral protection wire in transfemoral TAVI: a single-centre analysis of vascular complications - Marc Adrian Rogmann; Victor Klingemann; Max Meertens; Majid Ahoopai; Karl-Philipp Rommel; Philipp Lurz; Ralph S. von Bardeleben; Martin Geyer (Clinical Research in Cardiology, 2026)
Abstract Background Transfemoral transcatheter aortic valve implantation (TAVI) is the treatment of choice for severe aortic stenosis in patients with elevated surgical risk. However, vascular complications remain a major source of morbidity and mortality. The protection wire technique was introduced to prevent major access-related complications, but its role in contemporary TAVI practice is uncertain. Aims To evaluate whether routine protection wire use reduces vascular complications in contemporary transfemoral TAVI. Methods We performed a retrospective, single-centre analysis of 1476 consecutive patients undergoing transfemoral TAVI between January 2020 and August 2023. Until November 2021, protection wire placement was standard-of-care (Group 1, n = 801); thereafter procedures were performed without routine protection wire use (Group 2, n = 675). Vascular complications were defined according to VARC-3 criteria. Multivariable logistic regression was used to identify independent predictors of minor and major vascular complications. Results The composite of minor and major vascular complications occurred more frequently in Group 1 than in Group 2 (18.6% vs. 10.8%, p < 0.001). In Group 1, 34.8% of access-related complications were associated with the protection wire access. Major vascular complications were numerically less frequent in Group 2 (2.5% vs. 4.2%). Omission of routine protection wire placement was independently associated with a lower risk (OR 0.52, 95% CI 0.38–0.72, p < 0.001). Conclusion In contemporary transfemoral TAVI, routine protection wire use was not associated with reduced major vascular complications and was linked to a higher rate of minor access site injuries. These findings support a restrictive rather than routine use of protection wires in current practice.